KOMPLEKSITAS TUGAS SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Samhita, Bagus Meshawidiyatmika; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2017)
Obtain empiriical evidence on the effeect of budgetary particiipation and budgeetary slack complexity of the task in relation budgetary participation on budgetary slack merupaka purpose of this study. Sampliing technique in this research is purposive sampling techniques, the number of respondents in the study of 82 respondents. The analysis technique used is Moderated regression analysis (MRA). The research proves that the participation budgeting has a negativee and signifiicant impact on budgetary slack on BPR in Denpasar, and the complexity of the task and significantly weaken the negative relationship between budgetary participation and budgetary slack on BPR in Denpasar .This shows that the higher the level of participation in the process budget preparation, the level of budgetary slack will be decreased, and if the compilers of the budget at the BPR in Denpasar experienced the complexity of tasks and participate in the budgeting process, the budgetary slack will experience an increase
Keywords: Participation Budgeting, Budgtary Salck, Task complexity